Theoretical proposal: Degradation of energy in the hierarchical levels of any organization - Tarantino-Curseri, Salvatore (2018)
This brief work emphasizes the importance of interdisciplinarity, and is supported by thermodynamics in order to highlight the behavioral similarity between Prigogine´s dissipative structure and the management of any company’s organizational structure. Bearing this in mind and in the framework of the second law of thermodynamics, a theoretical proposal (proto-scientific hypothesis) is developed to determine “the degradation of energy in the hierarchical levels of any organization.”